The Contribution of Physical Activity, Physical Activity Enjoymen, Physical Fitness to the Interpersonal Peacefullness in Elementary School Students - Aries Dwi Wijayanto; Nurcholis Sunuyeko; Adi Sucipto (IKIP Budi Utomo Malang, 2022)
This study to analyze the contribution of physical activity to physical activity enjoyment, physical activity to physical fitness, physical activity enjoyment to physical fitness, physical activity enjoyment to interpersonal peacefulness, and the contribution of physical fitness to interpersonal peacefulness of elementary school students. This research is secondary research with a quantitative correlational design using the Internet Mediated Research (IMR) approach with a sample of 1224 elementary school students in Malang Regency. Data collection used a questionnaire instrument through the IMR. Data analysis used bivariate correlation tests, partial analysis, and multiple regression. The results showed that there was a contribution of physical activity to physical activity enjoyment with a correlation value of 0.116, the contribution of physical activity to physical fitness had a correlation value of 0.268, the contribution of physical activity to interpersonal peacefulness had a correlation value of 0.123, the contribution of physical activity enjoyment to physical fitness had a correlation value of 0.219, the contribution of joy exercising on interpersonal peacefulnesshas a correlation value of 0.473 and the contribution of physical fitness to interpersonal peacefulnesshas a correlation value of 0.174 and from the overall analysis it has a significance value of 0.000 and the R Square value is 0.230 which means having physical activity, physical activity enjoyment and physical fitness have a significant contribution on interpersonal peacefulness in elementary school level students by 23%. So it can be concluded that physical activity, physical activity enjoyment, and physical fitness have a contribution to interpersonal peacefulness in elementary school-level students in Malang Regency, with a contribution percentage of 23%, and the rest is influenced by other variables.